Cell Tracking in Cancer Immunotherapy - Perrin, Justine; Capitao, Marisa; Mougin-Degraef, Marie; Guérard, François; Faivre-Chauvet, Alain; Rbah-Vidal, Latifa; Gaschet, Joëlle; Guilloux, Yannick; Kraeber-Bodéré, Françoise; Chérel, Michel; Barbet, Jacques (Frontiers in Medicine, 2020)
The impressive development of immunotherapy in the last few years originates from a more precise understanding of control mechanisms in the immune system that leads to the discovery of new targets and new therapeutic tools. Indeed at different stages of disease progression elicit different local and systemic inflammatory responses, the ability to longitudinally interrogate the migration and expansion of immune cells throughout the whole body will greatly facilitate disease characterization and guide selection of appropriate treatment regiments. While using radiolabeled white blood cells to detect inflammatory lesions has been a classical nuclear medicine technique for years, new non-invasive methods for monitoring the distribution and migration of biologically active cells in living organisms have emerged. They are designed to improve the detection sensitivity and allow for a better preservation of cell activity and integrity. These methods include the monitoring of labeled therapeutic cells but also of all cells related to a specific disease or therapeutic approach. Labeling of therapeutic cells for imaging may now be performed in vitro, with some limitations on sensitivity and duration of observation. Alternatively, in vivo labeling may be performed by genetically engineered cells or mice that may be revealed in vivo through imaging. In addition, SPECT or PET imaging based on monoclonal antibodies have been used to detect tumors in the human body for years. They may be used to detect and possibly quantify the presence of specific cells within the lesions. These methods have been the object of several recent reviews that have concentrated on technical aspects, stressing the differences between direct and indirect labeling. They are described here by distinguishing ex vivo (labeling cells with paramagnetic, radioactive or fluorescent tracers) and in vivo (in vivo capture of radioactive, fluorescent or luminescent tracers injected, or directly by using labeled antibodies, ligands or pretargeted clickable substrates) imaging methods. Cell tracking in specific therapeutic applications, namely cell therapy, and particularly CAR (Chimeric Antigen Receptor) T-cell therapy, is a fast-growing research field with various therapeutic indications. The potential impact of imaging on the progress of these new therapeutic modalities is discussed.